Productive and Reproductive Perfomance of Dairy Cows During Peripartum - Pinto Neto,Adalgiza (2018)
ABSTRACT Dairy activity is of great importance for the national economy. It is also an important source of income for families in the south east region of Paraná that work in this area. There has been a notable expansion in the activities as well as in the quantity of production and the quality of the products. With this has come problems in the reproductive efficiency of the dairy cattle principally in relation to those with the greatest production. The objective of this study was to evaluate the productive profile and the reproductive efficiency of dairy cows. The evaluation covered 30 days before calving and 15, 30, 45, 60 and 90 days after the calving. The study covered cows from two properties in the Municipality of Realza-PR in Brazil. In order to do the aforementioned, we used the Body Condition Score (BCS). We evaluated the production of milk and through the use of gynecological exams and we looked at uterine involution (UI) and ovarian cyclicality. The results showed falls in the BCS in the prepartum period and in the first weeks of lactation (p<0.05) and the differences in the BCS were based on the season of the year in which the calving took place (p<0.05) with the highest BCS being noted to occur in the hot seasons. The UI correlates with the presence of corpus luteum where animals were late in their uterine involution and had delays in their first postpartum ovulation (p<0.05). The average service period and calving interval were similar to those described for dairy cattle, however, we observed variations based on the seasons of the year which was possibly related to the greater availability and quality of the forage in the hot seasons.